Rucaparib in relapsed, platinum-sensitive high-grade ovarian carcinoma (ARIEL2 Part 1): an international, multicentre, open-label, phase 2 trial - Swisher,EM; Lin,KK; Oza,AM; Scott,CL; Giordano,H; Sun,J; Konecny,GE; Coleman,RL; Tinker,AV; O'Malley,DM; Kristeleit,RS; Ma,L; et al. (Lancet Oncology, 2017)
BackgroundPoly(ADP-ribose) polymerase (PARP) inhibitors have activity in ovarian carcinomas with homologous recombination deficiency. Along with BRCA1 and BRCA2 (BRCA) mutations genomic loss of heterozygosity (LOH) might also represent homologous recombination deficiency. In ARIEL2, we assessed the ability of tumour genomic LOH, quantified with a next-generation sequencing assay, to predict response to rucaparib, an oral PARP inhibitor.MethodsARIEL2 is an international, multicentre, two-part, phase 2, open-label study done at 49 hospitals and cancer centres in Australia, Canada, France, Spain, the UK, and the USA. In ARIEL2 Part 1, patients with recurrent, platinum-sensitive, high-grade ovarian carcinoma were classified into one of three predefined homologous recombination deficiency subgroups on the basis of tumour mutational analysis: BRCA mutant (deleterious germline or somatic), BRCA wild-type and LOH high (LOH high group), or BRCA wild-type and LOH low (LOH low group). We prespecified a cutoff of 14% or more genomic LOH for LOH high. Patients began treatment with oral rucaparib at 600 mg twice per day for continuous 28 day cycles until disease progression or any other reason for discontinuation. The primary endpoint was progression-free survival. All patients treated with at least one dose of rucaparib were included in the safety analyses and all treated patients who were classified were included in the primary endpoint analysis. This trial is registered with ClinicalTrials.gov, number NCT01891344. Enrolment into ARIEL2 Part 1 is complete, although an extension (Part 2) is ongoing.Findings256 patients were screened and 206 were enrolled between Oct 30, 2013, and Dec 19, 2014. At the data cutoff date (Jan 18, 2016), 204 patients had received rucaparib, with 28 patients remaining in the study. 192 patients could be classified into one of the three predefined homologous recombination deficiency subgroups: BRCA mutant (n=40), LOH high (n=82), or LOH low (n=70). Tum